Comparison Of Slang In Millennials And Gen Z: A Semantic Analysis In The Context Of Linguistic Learning - Ana Juli; Marina Suci; Apriyani Esti (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to compare the semantic phenomena of slang used by the Millennial generation and Gen Z on social media. The main focus of this research is to identify the types of slang that are often used by both generations, as well as understanding the meaning and reasons for the use of slang by the Millennial generation. The method used in this research is descriptive qualitative, with data obtained through journal reviews and analysis of documentation from social media such as Facebook, X (formerly known as Twitter), and Instagram. This research found that there are significant differences in the types of slang used by the Millennial and Gen Z generations, which are influenced by cultural and technological developments. In addition, this research reveals that the main reason the Millennial generation uses slang on social media is to strengthen social ties, show familiarity, and follow trends. The use of slang is also considered a way to create a unique and relevant digital identity in their social environment.